Decolonising Citation: Indigenous Knowledge Attribution Toolkit and Australian Library Citational Practices - Thorpe, Kirsten; Faulkhead, Shannon; Booker, Lauren; Sentance, Nathan; Barrowcliffe, Rose (KULA)

(untitled) (University of Victoria Libraries, 2026)
This article examines the development of the Indigenous Referencing Guidance for Indigenous Knowledges within the broader context of decolonial practice in library and information studies. Academic citation practices have historically privileged Western knowledge frameworks while rendering Indigenous Knowledge systems invisible or subordinate. The Indigenous Referencing Guidance represents an intervention that seeks to address this imbalance by guiding ethical and accurate attribution of Indigenous Knowledge sources.Developed through a partnership between the Indigenous Archives Collective and CAVAL, the Indigenous Referencing Guidance for Indigenous Knowledges project created an Indigenous Knowledge Attribution Toolkit (IKAT) that includes two key components: a decision tree providing guidance for content assessment and attribution and a comprehensive citation and referencing guide featuring examples of Indigenous attribution methods. The guidance specifically addresses academic libraries working with Indigenous information sources at the undergraduate level by acknowledging the critical need to redress power imbalances in citation processes, ensure accurate attribution, and increase the representation of Indigenous knowledges in source materials.This paper outlines the principles underlying the development of the guide, describes the importance of using Indigenous research methodologies to guide ethical Indigenous research practices, and addresses the politics of citation. It explores the opportunities to elevate Indigenous Knowledges through citational practices by sharing examples of practical applications and use of sources described in the IKAT. By considering citations in the context of them being respectful and relational practices, the guide elevates the recognition of Indigenous Knowledges. In doing this, the IKAT specifically contributes to broader movements for Indigenous Data Sovereignty, supports the implementation of Right of Reply protocols, and advances Indigenous priorities in library and academic citation practices. The article concludes by discussing the opportunities connected with implementing the IKAT and suggests future directions for evolving citation practices that honour Indigenous Knowledges.